Development of Local Content E-Module of Sebimbing Sekundang Dance with Inquiry Learning Model on Movement System Material to Improve Science Literacy and Student Learning Motivation - Amalia Desma Triani; Nur Aeni Ariyanti (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2025)
This study aims to determine the validity, practicality, and effectiveness of the local content E-Module for the Sebimbing Sekundang dance, using an inquiry learning model on movement system material, to improve scientific literacy and students' learning motivation. This type of research is a development project using the ADDIE model and an equivalent control group design. The E-Module product was evaluated by media expert lecturers, material experts, practitioners, and tested on a limited number of 36 grade XII students. The population of this study comprised grade XI students of SMAN 01 OKU: XI.2 as the control class (36 students) and XI.4 as the experimental class (36 students), selected by random sampling. The instruments used were interviews, observations, student needs questionnaires, media expert and material expert validation questionnaires, practitioner validation questionnaires, student practicality response questionnaires, observation of learning implementation, science literacy test questions, and learning motivation. Data analysis techniques used normality tests, homogeneity tests, multivariate tests, and N-Gain tests. The results of the study showed that the E-Module was highly valid for use as a teaching material, with media experts rating it 92% (very feasible) and material experts rating it 96.51% (very feasible). In addition, the E-Module was rated very practical by biology teachers (95.71%) and by students (83.5%). The use of E-Modules was very effective in improving scientific literacy and student learning motivation with a Sig. value of 0.00 <0.05 and an N-Gain score of 0.73 included in the high category for scientific literacy, and 0.76 included in the high category for learning motivation. In conclusion, the local content E-Module of Sebimbing Sekundang dance is valid, practical, and effective in increasing scientific literacy and students' learning motivation.